Hubungan Indeks Massa Tubuh dan Persen Lemak Total Dengan Kadar Gula Darah Sewaktu Pada Pasien Diabetes Mellitus Tipe II di UPTD Puskesmas Kotaagung Tahun 2024 - Nuzila Meysa Rhasetia; Desti Ambar Wati; Mayesti Akhriani; Lara Ayu Lestari (Universitas Airlangga, 2025)
Background: The chronic metabolic condition known as type There is a positive correlation between the risk of developing type 2 diabetes mellitus and Body Mass Index (BMI) and body fat percentage. Signs of type 2 diabetes mellitus are hyperglycemia caused by insulin resistance or insulin deficiency. Pro-inflammatory adipokines are produced as adiposity increases, which interferes with insulin sensitivity, causing blood glucose to accumulate. As a result, the body has difficulty absorbing blood sugar. When blood sugar continues to rise, diabetes develops. Objectives: This study aimed to determine the correlation between Body Mass Index (BMI), total body fat percentage, and random blood glucose levels in individuals with Type 2 Diabetes Mellitus. Methods: This study used a cross-sectional approach, an analytical design, and quantitative methodology. The research was conducted at the Kotaagung Public Health Centre from October to December 2024 with a population of 87 and a research sample of 58 Diabetes Mellitus patients using the method of random sampling. A questionnaire was employed as the research tool, measuring body weight and body fat percentage with a Karada scan tool, measuring height using a microtome, and measuring blood sugar levels with a glucometer. Data analysis used the Pearson test. Results: The respondent characteristics by gender showed 19 men (32.8%) and 39 women (67.2%). The mean Body Mass Index (BMI) was 22.23±3.25 kg/m² for men and 25.36±3.58 kg/m² for women. For total body fat percentage, the mean was 20.93±2.95% for men and 36.65±5.82% for women. The mean Random Blood Glucose (RBG) level was 211.00±67.4 mg/dL for men and 258.05±96.24 mg/dL for women. Conclusion: In type 2 diabetes patients treated at Kotaagung Health Center, there was a correlation between random blood sugar levels with body mass index and body fat percentage, with a p-value=0.000.